Combination of Jelly Bump and Protein Deposits in a Conventional Prosthetic Contact Lens: A Rare Case Report - Suraj Kumar Chaurasiya; Sanjay Chanda; Mayank Sharma (Delhi Journal of Ophthalmology)
A 38-year-old male prosthetic contact lens (CL) wearer developed foreign-body sensation in the right socket which on examination showed a rare combination of jelly bump and protein deposits on the prosthetic CL. The continuous wear for 5 months without removal and nonadherence to the lens care regimen led to multiple raised circular bumps with dry looking lens surface and significant protein film accumulation. Slit-lamp examination identified these deposits as a combination of protein and jelly bumps deposits. The deposits, primarily composed of lipids and calcium, are linked to high-water-content hydrogel lenses. The case highlights the importance of proper lens care and regular follow-up. Transitioning to low-water-content, nonionic lenses may help reduce such deposits and improve patient comfort.